Characterization and Treatment Goals of Patients on Long-Acting Injectable vs Oral Antipsychotics: Results from a Patient/Caregiver/Psychiatrist Survey. (April 2021) - Fitzgerald, Heather M.; Shepherd, Jason; Bailey, Hollie; Berry, Mia; Wright, Jack; Chen, Maxine
Abstract: Background: Patient preferences in schizophrenia (SCZ), including identification of key goals and outcomes for treatment and relative importance of certain treatment goals to patients, have been assessed by several studies. However, there continues to be a lack of sufficient evidence on US patient attitudes and perceptions towards treatment goals and pharmacotherapy options in SCZ, especially taking into context long-acting injectable antipsychotics (LAIs) in this disease area. This lack of evidence is further pronounced in caregivers of individuals with SCZ. The objective of this analysis was to characterize patients with SCZ on LAIs vs patients on oral antipsychotics (OAPs) and evaluate the treatment goals of patients in each group. Methods: This was a real-world, cross-sectional survey of US psychiatrists, patients =18 years old with a diagnosis of SCZ, and caregivers. Data was collected using the Disease Specific Programme (DSP) methodology, which has been previously published. Psychiatrists (n=120) completed detailed record forms for next 8 consecutive outpatients and 2 inpatients matching inclusion criteria, including non-interventional clinical and subjective assessments. The same patients and their caregivers, if present, were invited by their psychiatrist to voluntarily complete a separate survey. Results: Of 1135 patients on treatment where the physician provided survey data; 251 were on an LAI, and 884 were on an OAP. Mean (SD) time to SCZ diagnosis for those on an LAI was 10.3 (12.0) years vs 7.8 (10.5) years for those on OAPs. More patients in the LAI vs OAP group were being treated as an inpatient (27.1% vs 15.7%, respectively; p<0.0001). Patients on an LAI reported being on their current medication regimen for less time (mean 1.7 years) vs those on OAPs (mean 2.5 years) (p=0.0093). More patients on LAIs were unemployed due to disability vs those on OAPs (56.1% vs 39.5%, respectively), and less patients on LAIs were able to work part-time or full-time (21.1% or 4.1%) vs those on OAPs (23.2% or 11.4%). More patients on an LAI had a caregiver vs those on OAPs (37.3% vs 26.1%, respectively; p=0.0011). Regarding the most important treatment goals reported by patients, both groups reported similar preferences for decrease in disease symptoms (62% on LAI vs 65% on OAPs) and thinking more clearly (53% on LAI vs 46% on OAPs); however, a numerically higher proportion of LAI patients reported that the current medication helped decrease hospitalizations due to relapse vs those on OAPs (38% vs 32%, respectively). Discussion: Given the characteristics of patients participating in this real-world survey, those on LAIs exhibited qualities which indicate a higher severity of illness vs those on OAPs. Results suggest that treatment with LAIs is still mainly being provided to patients later in the disease course and/or who have adherence problems, despite a growing body of evidence of utility in younger patients earlier in the course of illness. Funding: Otsuka Pharmaceutical Development & Commercialization, Inc. and Lundbeck LLC